2017
DOI: 10.1002/2016jd026436
|View full text |Cite
|
Sign up to set email alerts
|

Impact of assimilating GOES imager clear‐sky radiance with a rapid refresh assimilation system for convection‐permitting forecast over Mexico

Abstract: The Geostationary Operational Environmental Satellite (GOES) imager data could provide a continuous image of the evolutionary pattern of severe weather phenomena with its high spatial and temporal resolution. The capability to assimilate the GOES imager radiances has been developed within the Weather Research and Forecasting model's data assimilation system. Compared to the benchmark experiment with no GOES imager data, the impact of assimilating GOES imager radiances on the analysis and forecast of convective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…We focus on assimilating AHI radiances at convective scales in this study as a follow on work of Yang et al (), who assimilated GOES imager radiances based on an operational hybrid 3‐D ensemble‐variational DA system using a 4 km configuration over a Mexico domain. In contrast with Yang et al (), this work is based on the operational 3DVar system of the Northeast China regional NWP center operated by the Liaoning Meteorological Bureau of China Meteorological Administration. Since there is much more land coverage in our domain, the radiances from three AHI water vapor channels (6.2, 6.9, and 7.3 μm) are chosen for assimilation because the other infrared channels are sensitive to land surface emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on assimilating AHI radiances at convective scales in this study as a follow on work of Yang et al (), who assimilated GOES imager radiances based on an operational hybrid 3‐D ensemble‐variational DA system using a 4 km configuration over a Mexico domain. In contrast with Yang et al (), this work is based on the operational 3DVar system of the Northeast China regional NWP center operated by the Liaoning Meteorological Bureau of China Meteorological Administration. Since there is much more land coverage in our domain, the radiances from three AHI water vapor channels (6.2, 6.9, and 7.3 μm) are chosen for assimilation because the other infrared channels are sensitive to land surface emission.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that SEVIRI radiances had a positive impact on the very short range forecast. Yang et al () assimilated GOES imager radiances using the Weather Research and Forecasting (WRF) DA system (Barker et al, ) for convection‐permitting (4 km) forecasting over Mexico and obtained some significant positive results.…”
Section: Introductionmentioning
confidence: 99%
“…But for the hourly rapid update system, the 3-hourly global ensemble is not enough. In this situation, we can utilize the interpolation of the 3-hourly global ensemble to the hourly global ensemble as Yang et al (2017) [32] did, the time-expanded ensembles as Zhao et al 2015 [19] did, or a time-lagged ensemble as Wang et al 2017 [21] did. Furthermore, as the resolution of global ensemble in time and space will be increased in the future, the augmented global error covariance can be used for the rapid updated regional convective-permitting NWP.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Results show a positive impact for almost all upper-air variables; the main improvements are obtained for geopotential height and humidity [29][30][31]. The impact of assimilating Geostationary Operational Environmental Satellite (GOES) imager radiances on the analysis and forecast of a convective process over Mexico was assessed for the first time using a rapid refresh assimilation system with a convection permitting model setting [32]. Improved humidity and temperature analysis and significant standard deviation reductions were produced when the assimilation is activated [32].…”
Section: Introductionmentioning
confidence: 99%